Mortality and morbidity costs of road traffic-based air pollution in Turkey. (September 2021) - Ara Aksoy, Shihomi; Kiziltan, Anna; Kiziltan, Mustafa; Aydınalp Köksal, Merih; Öztürk, Fatma; Tekeli, Ş. Elçin; Aslanoğlu, S. Yeşer; Im, Ulas; Duran, Nilhan; Ünal, Alper; Baykara, Metin; Özyürek, Nazan; et al.
Abstract: Government policies on renewing vehicle fleet by introducing newer, cleaner vehicles and removing old, polluting vehicles have significant impacts on air pollution. In this study, the estimated emissions of air pollutants that influence human health are reported together with health endpoints and corresponding mortality and morbidity costs under five alternative road transport policy scenarios, varying in scrapping rate and the shares of hybrid and electric vehicles. Using COPERT software, PM10, PM2.5, NO2, and SO2 emissions are determined for five scenarios. PM2.5 is the most reduced pollutant (41%) if the government adopts the most progressive scenario, followed by PM10 (27%) and NO2 (27%). A total of a maximum of 19, 396 premature deaths and 803, 328 years of life lost could be saved, corresponding to 252 billion TL cost savings over the 2020–2030 period if the most drastic policy encouraging an introduction of the newer and cleaner vehicles is adopted. HIGHLIGHTS: One business-as-usual and four alternative scenarios to reduce road-traffic based air pollution are analyzed in terms of emission, mortality and morbidity, and health costs. Maximum potential reductions for PM2.5, PM10, and NOx are estimated at 41%, 27%, 27%, respectively. Acute mortality can be reduced by a minimum of 9241 cases and a maximum of 19, 396 in 2020–2030. A maximum of 803, 328 Years of Life Lost can be saved compared with business-as-usual (BAU) as a total. The total potential health cost saving is between 112 billion and 252 billion TL compared with BAU.